2019
DOI: 10.7759/cureus.5764
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Choreoathetosis in a Patient with End-stage Renal Disease from Administration of Ceftriaxone

Abstract: A wide spectrum of neurological manifestations may be induced in patients with impaired renal function when receiving beta-lactam antibiotics due to the altered pharmacokinetics. Beta-lactam antibiotics is commonly chosen for treatment in patients with end-stage renal disease due to its good penetration into the cerebrospinal fluid and long half-life.Here, we present a case of a 73-year-old Malay lady with end-stage renal disease who was admitted for treatment of gastroenteritis. She presented with acute onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…We did a literature review on PubMed in April 2023 without a time limit and identified 15 case reports,4 6–9 11–13 15–18 20 21 26 7 small case series2 3 5 10 14 19 27 and 2 pharmacovigilance database analysis22 28 discussing serious neurological effects of ceftriaxone in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did a literature review on PubMed in April 2023 without a time limit and identified 15 case reports,4 6–9 11–13 15–18 20 21 26 7 small case series2 3 5 10 14 19 27 and 2 pharmacovigilance database analysis22 28 discussing serious neurological effects of ceftriaxone in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Ceftriaxone-related adverse neurological effects are uncommon to very rare and mostly mild (dizziness, headache, ataxia, paresthesia) 1. However, multiple case reports2–21 and a case series from a French pharmacovigilance database22 have been published on more severe reactions, notably encephalopathy, trouble of consciousness and choreoathetosis. With ceftriaxone being one of the most commonly used parenteral antibiotics worldwide23, there is a possibility that many more cases of these severe adverse reactions are not readily recognised or may be confused with common delirium.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated the influence of the kidney functional state on toxicity and how ceftriaxone led to side effects ( Kim et al, 2012 ; Safadi et al, 2014 ; Tan and Tun, 2019 ; Yamada et al, 2020 ; Oyama et al, 2021 ). For instance, a case series reported that ceftriaxone treatment for a long period at high dosages was associated with the development of pseudolithiasis in patients with severe renal impairment who received dialysis ( Oyama et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…[2,9] An alternate hypothesis is that ceftriaxone causes the release of inflammatory cytokines like tumor necrosis factor-alpha which triggers neurotoxicity. [14] Renal impairment [1,3,5,7,9,10,11,13,15] and old age [1,3,5,7,9,10,13,15] are the main predisposing factors observed in most patients diagnosed with CIE in the literature. Hepatic dysfunction, [5] impaired biliary excretion, [3] administration of high-dose ceftriaxone, [8] and preexisting neurological conditions [1,12] are the other risk factors associated with CIE. Cerebrovascular disease, [10,14] meningitis, [8] and cerebral contusion [15] are the neurological conditions that have been reported to predispose to CIE. e risk factors in the case we present are old age and the presence of a multicentric glioma.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 , 9 ] An alternate hypothesis is that ceftriaxone causes the release of inflammatory cytokines like tumor necrosis factor-alpha which triggers neurotoxicity. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%